2021
DOI: 10.1186/s12887-021-02608-0
|View full text |Cite
|
Sign up to set email alerts
|

Virologic response of treatment experienced HIV-infected Ugandan children and adolescents on NNRTI based first-line regimen, previously monitored without viral load

Abstract: Background Many HIV-infected African children gained access to antiretroviral treatment (ART) through expansion of PEPFAR programs since 2004 and introduction of “Test and Treat” WHO guidelines in 2015. As ART access increases and children transition from adolescence to adulthood, treatment failure is inevitable. Viral load (VL) monitoring in Uganda was introduced in 2016 replacing clinical monitoring. However, there’s limited data on the comparative effectiveness of these two strategies among … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our analysis showed that VF rates were lowest in the rapid treatment group and highest in those initiating ART between 1–3 months, and >3 months after diagnosis. A study from 26 countries demonstrated that regular VL monitoring in adolescents has increased in low/lower‐middle‐income countries after the adoption of treat all policies, and is critical for the early detection of treatment failure [ 36 , 37 , 38 ]. Furthermore, YLHIV who started ART rapidly had a lower risk of switching to second‐line ART compared to other ART initiation groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that VF rates were lowest in the rapid treatment group and highest in those initiating ART between 1–3 months, and >3 months after diagnosis. A study from 26 countries demonstrated that regular VL monitoring in adolescents has increased in low/lower‐middle‐income countries after the adoption of treat all policies, and is critical for the early detection of treatment failure [ 36 , 37 , 38 ]. Furthermore, YLHIV who started ART rapidly had a lower risk of switching to second‐line ART compared to other ART initiation groups.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The need for life-long therapy requires the availability of potent ARV regimens that are well-tolerated because virologic failure and drug resistance is unfortunately common among children and adolescents. [4][5][6][7][8] In addition, significant concerns remain regarding toxicities associated with widely used ARVs, including neuropsychiatric toxicities with efavirenz, gastrointestinal toxicities such as diarrhea with multiple protease inhibitors (PIs), weight gain with integrase strand transfer inhibitors (INSTIs), and serum lipid abnormalities associated with multiple ARV classes. Thus, potent treatment regimens that have excellent safety and tolerability profiles and are convenient are still highly desirable.…”
Section: Introductionmentioning
confidence: 99%